Please solve If p = –2 and q = –1, evaluate 3p2 + 3q.?



Answers:
Well
3(-2)2+ 3(-1)=

-12 + -3 = -15
-12 + -3 = -15
3p2 + 3q= 3*-2*2 + 3*-1 = -12-3= -15.
the answer is -15
3p2 + 3q

__just change the symbols with their value
3(-2)2 + 3(-1)

__i suppose the value 2 after p means square, not multiple by 2... ^_^'
so the result is..
3(-2)2 + 3(-1)
= 3(-2)(-2) + 3(-1)
= 12 -3
= 9

hope this help! =D
3(-2)2+3(-1)
( 3*-2)*2+(3*-1)
(-6*2)+-3
-12+-3
equals15.
=3*(-2)*2+3(-1)
=-12+(-3)
=-15

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.



More Questions & Answers...
  • What is the pH of 0.35M of HCl??
  • How does the government influence teens today?
  • A certain triangle has an area of 2ysquared + 15y + 7 divided by 2.?
  • What is the theme of the book "In Cold Blood"?
  • Math Problems (Metric)?
  • What does this saying imply "The glory that was greece and the grandeur that was rome"?
  • Please help me with my math homework! Will give points to best answer!?
  • PLEASE ANSWER A.S.A.P!!! I need help writing this paper that's due tomorrow?
  • Copyright 2006-2009 EduQnA.com All Rights Reserved.